2009
DOI: 10.2322/tjsass.52.74
|View full text |Cite
|
Sign up to set email alerts
|

Airfoil Tonal Noise Generation in Resonant Environments

Abstract: To clarify tonal noise generation, an experimental study on airfoil tonal noise was undertaken using a conventional wind tunnel, which allows acoustic reflection on test section walls. A two-dimensional wing model with the NACA0015 cross-section was used at 5 degrees angle of attack. Most previous experiments conducted in anechoic environments commonly show that the tonal noise frequency is selected in an overall trend of U 1:5 (U is uniform velocity) locally consisting of a step-like structure, and Tollmien-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 7 publications
1
15
1
Order By: Relevance
“…8, the moderate peak consisting of broadband disturbances peaking at about 270 Hz, which is very close to the frequency of the tonal noise, is obviously not attributable to T-S instabilities. This is consistent with our previous observations, 1) which concluded that the broadband disturbances originate from hydrodynamic instability of the inflectional velocity profile and as a consequence, visualized flow motions show that unsteady disturbances seem to be sequentially magnified during a half period, after the turbulent boundary layer is shed from the suction side of airfoil. The top spectrum is the natural case and the bottom with À20 dB shift is the artificially disturbed case.…”
Section: )supporting
confidence: 81%
See 2 more Smart Citations
“…8, the moderate peak consisting of broadband disturbances peaking at about 270 Hz, which is very close to the frequency of the tonal noise, is obviously not attributable to T-S instabilities. This is consistent with our previous observations, 1) which concluded that the broadband disturbances originate from hydrodynamic instability of the inflectional velocity profile and as a consequence, visualized flow motions show that unsteady disturbances seem to be sequentially magnified during a half period, after the turbulent boundary layer is shed from the suction side of airfoil. The top spectrum is the natural case and the bottom with À20 dB shift is the artificially disturbed case.…”
Section: )supporting
confidence: 81%
“…The reason why acoustic sound is discrete is ascribed to feedback loops between the T-E noise and T-S waves, although T-S instability is inherently unstable with respect to broadband disturbances. However, this explanation does not cover the case where T-S instabilities are subcritical at very low Reynolds numbers, as reported by Nakashima et al 6) In addition, the experiments by Atobe et al 1) and Kobayashi et al 7) showed no T-S waves in generation of tonal noise, even for natural moderate Reynolds numbers. It appears that the mechanism of tonal noise generation from the trailing edge might be complex.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…A notable exception is the data set of Chong & Joseph (2012), which shows a dependency on u 0.8 scaling over very small ranges of Reynolds number only, indicating a finer 'ladder' structure. Also the data of Atobe et al (2009) (not shown here) shows a different, namely constant scaling. Therefore, it appears that different types of 'ladder' structures might be associated with different mechanisms, as noted before by Tam & Ju (2012).…”
Section: Scaling Of Tonal Frequencymentioning
confidence: 82%
“…The study of Atobe, Tuinstra & Takagi (2009), conducted in a resonant environment, showed a fundamentally different velocity dependence. In contrast to the experiments conducted in anechoic facilities, tonal frequencies were reported to remain constant with increasing velocity, which was attributed to resonance effects.…”
Section: Early Observations and Scaling Rulesmentioning
confidence: 99%